Antibacterial activity extract fraction of black garlic against bacteria propionibacterium acnes with disc diffusion method - Rensiana Kartini Pandi; Elisabeth Oriana Jawa La; Ni Ketut Esati (Health Sciences and Pharmacy Journal, 2022)
Black garlic is the result of processing garlic through a heating process at a temperature of 70oC with a relative humidity of 70-80% for 21 days without additional treatment so that the water content decreases. Black garlic has antibacterial activity due to the presence of bioactive compounds from the phenolic and flavonoid groups. This study aims to determine the secondary metabolite content and antibacterial activity of the black garlic extract fraction against Propionibacterium acnes bacteria. Extraction of Black garlic by maceration method used 96% ethanol as solvent and to obtain extract fraction of Black garlic by multilevel fractionation method using n-hexane, ethyl acetate, and ethanol as solvents. To determine the content of secondary metabolites, phytochemical screening was carried out in each fraction. Antibacterial activity test of Propionibacerium acnes used disc diffusion method with various concentrations of n-hexane, ethyl acetate, ethanol fractions 2%, 4%, 6%, 8%, 10%, positive control (clindamycin 1%), negative control and media control. Data analysis was carried out with qualitative, quantitative, and statistical analysis. The results obtained were the extract fraction of black garlic contains secondary metabolites of flavonoids, alkaloids, saponins, and tannins. The results of the antibacterial activity test showed that the garlic extract fraction had antibacterial activity seen from the presence of an inhibition zone. The largest inhibition zone in the n-hexane fraction of 10% concentration of 8.50 ± 0.10 mm was included in the medium category. The positive control was 12.02 ± 1.41 mm and the negative control gave no inhibition zone.